ANALISIS EFEKTIVITAS DIGITALISASI ADMINISTRASI PERTANAHAN MELALUI APLIKASI PROTADES DI DESA KEPUH KECAMATAN LIMPUNG KABUPATEN BATANG - Pramesty Sanggita Cahyani; Wijayanto Wijayanto (Journal of Politic and Government Studies, 2026)
Land administration at the village level serves as a vital foundation in ensuring legal certainty of land ownership for the community. However, Kepuh Village faces serious obstacles due to the use of manual Letter C Books that are obsolete, damaged, and difficult to read, which hinders the speed of public services. This study aims to analyze the effectiveness of digitalizing land administration through the implementation of the Protades application in Kepuh Village, Limpung District, Batang Regency. The method used is qualitative descriptive, with data collection techniques including in-depth interviews, observation, and documentation studies involving village officials and the community. The research results indicate that the implementation of Protades has improved internal work efficiency through more secure and systematic digital data restoration. The use of this application significantly accelerates the process of searching for land parcel data compared to conventional methods. Nevertheless, the effectiveness of this digitalization remains partial as it does not yet include the provision of online self-service for residents, meaning that service interactions still fully depend on physical presence at the village office. The primary obstacles identified include the limited digital literacy of the community and the need for continuous technical capacity building for village officials. This study concludes that while Protades is highly effective in securing vital village archives, a comprehensive transformation toward digital public services still requires the development of accessibility for the broader community.